Fiqh Al-Muwazanah as a Governance Oriented Framework for Digitally Mediated Marriege in Islamic Family Law - Helmi Basri; Mukhlis Lubis (FASYA Press, 2025)
There is a literature exploring how these digitally mediated marriages are managed within a governance framework to mitigate long-term legal and social risks. No studies have specifically utilized the instrument of Fiqh Al-Muwazanah as an ethical and managerial basis for ensuring legal certainty in a digital ecosystem vulnerable to identity manipulation and technical failures. This fiqh al-muwÄzanah, the jurisprudence of balancing benefits (maá¹£laá¸¥ah) and harms (mafsadah), as a governance-oriented risk-assessment framework for digitally mediated marriage practices. Employing a conceptual approach statute approach method with a maqÄá¹£id-oriented doctrinal approach, the study critically reinterprets ittiá¸¥Äd al-majlis by shifting its emphasis from physical co-presence to legal continuity and procedural certainty. The analysis demonstrates that digital presence may conditionally satisfy the objectives of ittiá¸¥Äd al-majlis where real-time interaction, verifiable identity, reliable witnessing, and safeguards against coercion are effectively ensured. However, such accommodation is framed as exceptional rather than normative, particularly considering risks affecting consent, evidentiary reliability, and the protection of vulnerable parties. Beyond the specific issue of online marriage, this study contributes to contemporary Islamic legal theory by demonstrating how fiqh al-muwÄzanah can function as a structured mode of legal reasoning capable of governing technological change within legally plural systems. novelty by reconstructing the role of Fiqh Al-Muwazanah not merely as an abstract legal theory, but as an operational (governance-oriented) framework for digitally mediated marriages. Unlike conventional approaches, this paper proposes new parameters in Islamic family law that balance technological convenience (taysir) with the protection of the purposes of marriage (maqasid al-nikah) through digital risk mapping.